The Influence of Convenience & Trust on the Decision to Use the QRIS Payment System in Bangli District - Luh Putu Nindia Sastiari; Ni Ketut Seminari (Digital Innovation : International Journal of Management, 2024)
Technological developments in payment systems that are being encouraged by the government lately involve the emergence of payment instruments known as electronic money (e-money) and virtual money (virtual money). QRIS is a QR code standard for digital payments through server-based electronic money applications, electronic wallets, or mobile banking. This study aims to determine the effect of convenience, trust on usage decisions. The sample in this study used respondents who live in Bangli and are Generation Y and Generation Z who are 17 years and over as many as 84 consumers. The data analysis technique uses Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, F Test and T Test. From the research results obtained, the results of convenience have a positive and significant effect on the decision to use, trust has a positive and significant effect on the decision to use and convenience and trust have a positive and significant effect on the decision to use. Suggestions that can be given by researchers are that it is hoped that the QRIS manager will periodically make updates to QRIS, the QRIS manager provides complete information on social media or the official QRIS website so that later all the information needed by QRIS users is available and continues to add places that provide QRIS payment methods.